Microreactor production by PolyJet Matrix 3D-printing technology hydrodynamic characterization - Šercer, Mladen; Rezić, Tonči; Godec, Damir; Oros, Damir; Pilipović, Ana; Ivušić, Franjo; Rezić, Iva; Andlar, Martina; Ludwig, Roland; Šantek, Božidar (2019)
This work investigates the methodology of producing a 3D-printed microreactor from the acrylic resin by PolyJet Matrix process. The PolyJet Matrix technology employs different materials or their combinations to generate 3D-printed structures, from small ones to complex geometries, with different material properties. Experimental and numerical methods served for the evaluation of the geometry and production of the microreactor and its hydrodynamic characterization. The operational limits of the single-phase flow in the microchannels, further improvements and possible applications of the microreactor were assessed based on the hydrodynamic characterization.
U ovom je radu ispitana metodologija proizvodnje mikroreaktora iz akrilne smole pomoću PolyJet Matrix 3D ispita. PolyJet Matrix tehnologija koristi različite materijale ili kombinacije materijala radi tiskanja jednostavnih ili složenih 3D struktura različitih svojstava. korištene su Za procjenu geometrije, postupaka proizvodnje i hidrodinamičku karakterizaciju mikroreaktora upotrijebljene su eksperimentalne i numeričke metode. Na osnovi hidrodinamičke karakterizacije određene su procesne granice jednofaznog protoka u mikrokanalima, te je ispitana mogućnost daljnjih poboljšanja i primjene mikroreaktora.
Bibliografija: 35 jed.
Summary ; Sažetak.
Keywords: Mikroreaktori -- 3D printanje -- Hidrodinamička karakterizacija -- Akrilna smola